Common mental disorders in medical students: prevalence and associated factors - Carolina Martinho Cunha; Daniel Albuquerque Fortes; João Pedro Resende Scapim; Kionna Oliveira Bernardes Santos; Rita de Cássia Pereira Fernandes (Revista Brasileira de Educação Médica, 2023)
Abstract Objectives: This study aimed to estimate the prevalence of Common Mental Disorders (CMD) among medical students and identify the factors associated with this disorder. Methods: A cross-sectional study was conducted with all medical students, enrolled from the 1st to the 8th semesters in a public university, in the state of Bahia, Brazil. We used a self-administered questionnaire that included SRQ-20 (Self-Reporting Questionnaire), IPAQ (International Physical Activity Questionnaire - long form) and sociodemographic, school, occupational and health variables. The multivariate analysis was performed using COX Regression for cross-sectional studies. Results: We evaluated 556 students (289 women and 267 men), representing 90.2% of the target population. The overall prevalence of CMD found was 53.3%, 78.8% of students reported feeling nervous, 56.8% experienced poor sleep quality, and 6.5% had suicidal thoughts. After the multivariate analysis, the following factors maintained their association with a higher prevalence of CMD: having no previous undergraduate degree (PR=1.49), having an unfavorable self-perception of health (PR=1.53), not having failed disciplines (PR=1.20), and being a smoker (PR=1.19). Physical activity did not have a protective effect on CMD in this study. Conclusions: The prevalence of CMD among medical students was high and mainly associated with an unfavorable self-perception of health. The results highlight the need for strengthening institutional policies aimed at preventing psychological distress among students.